How I treat Waldenström macroglobulinemia - Dimopoulos, Meletios A; Kastritis, Efstathios (Blood, 2019)
Waldenström macroglobulinemia (WM) is an uncommon lymphoma characterized by the infiltration of the bone marrow by clonal lymphoplasmacytic cells that produce monoclonal immunoglobulin M (IgM). The disease may have an asymptomatic phase, or patients may present with symptoms and complications resulting from marrow or other tissue infiltration, or from physicochemical or immunological properties of the monoclonal IgM. Diagnosis of WM has been clearly defined, and genetic testing for somatic mutation of MYD88L265P is a useful tool for differential diagnosis from other conditions. Specific criteria that define symptomatic disease that needs treatment offer clinical guidance. The treatment of WM has evolved rapidly, with treatment options that include anti-CD20 monoclonal antibody-based combinations and BTK inhibitors. The choice of therapy is based on the need for rapid disease control, presence of specific disease complications, and patient's age. With the use of BTK inhibitors, the use of continuous therapy has been introduced as another option over fixed-duration chemoimmunotherapy. In this review, we focus on different clinical scenarios and discuss treatment options, based on the available data.